2013
DOI: 10.5194/angeo-31-263-2013
|View full text |Cite
|
Sign up to set email alerts
|

Variability of ionospheric TEC during solar and geomagnetic minima (2008 and 2009): external high speed stream drivers

Abstract: We study solar wind–ionosphere coupling through the late declining phase/solar minimum and geomagnetic minimum phases during the last solar cycle (SC23) – 2008 and 2009. This interval was characterized by sequences of high-speed solar wind streams (HSSs). The concomitant geomagnetic response was moderate geomagnetic storms and high-intensity, long-duration continuous auroral activity (HILDCAA) events. The JPL Global Ionospheric Map (GIM) software and the GPS total electron content (TEC) database were used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 72 publications
2
54
0
Order By: Relevance
“…These studies point to certain aspects of research that deserve close attention, such as a minimum in geomagnetic activity related to low solar and interplanetary magnetic fields and the disappearance of low-latitude coronal holes (Tsurutani et al, 2011), response of the ionosphere to extremely low solar EUV irradiance (Liu et al, 2011a, b), as well as the considerable energy input of high-speed solar wind streams (HSSs) and its impact on the thermosphereionosphere system (Lei et al, 2008a, b;Verkhoglyadova et al, 2013).…”
Section: Vision For Solar Cycle 24 and Beyondmentioning
confidence: 99%
“…These studies point to certain aspects of research that deserve close attention, such as a minimum in geomagnetic activity related to low solar and interplanetary magnetic fields and the disappearance of low-latitude coronal holes (Tsurutani et al, 2011), response of the ionosphere to extremely low solar EUV irradiance (Liu et al, 2011a, b), as well as the considerable energy input of high-speed solar wind streams (HSSs) and its impact on the thermosphereionosphere system (Lei et al, 2008a, b;Verkhoglyadova et al, 2013).…”
Section: Vision For Solar Cycle 24 and Beyondmentioning
confidence: 99%
“…Thus, CODE‐GIM provides an effective tool to study the ionospheric variation over varied scales. For example, in recent past, GIMs have been efficiently applied to understand variety of ionospheric phenomena ranging from effects of extreme events due to space weather [ Maltseva et al , ; Verkhoglyadova et al , ] and earthquake [ Zhao et al , ], forcing to quiet time mean variations of diurnal [ Shim et al ., 2008], seasonal and solar cycle scales [ Liu et al ., ] and effect of solar terminator [ Afraimovich et al , ], retrieval of electron density profiles [ Yue et al , ; Gulyaeva et al , ], and last but not the least for climatic variations in ionosphere [ Liu et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies, however, were focused on strong to severe storm events [e.g., Prölss , , ; Fuller‐Rowell et al ., ; Mendillo , , Mendillo and Narvaez , ; Wang et al ., ; Zhao et al ., , ; Lu et al ., ]. Recently, researchers began to pay more attention to ionosphere variations associated with weak to moderate geomagnetic activity driven by coronal hole high‐speed streams (HSS/CIR) [ Wang et al ., ; Burns et al ., ; Solomon et al ., ; Liu et al ., ; Verkhoglyadova et al ., ] when more ionospheric data became available and HSS/CIR‐associated geomagnetic activity occurred periodically and frequently during the declining phase of the last solar cycle. Burns et al .…”
Section: Introductionmentioning
confidence: 99%
“…Verkhoglyadova et al . [] studied the variability of ionospheric TEC during 2008–2009 and showed that the daily averaged vertical TEC in middle to low latitudes increased by 60% on average during HSS/CIR events.…”
Section: Introductionmentioning
confidence: 99%